The Huida-kwul-ra, or, Native tobacco of the Queen Charlotte Haidas [electronic resource] - Deans, James. ([S.l. : s.n., 1890)
Signed: James Deans. From: The American antiquarian and orienta1 journa1, vo1. XII, 1890. Caption tit1e. Electronic reproduction. Mode of access: Internet. 44